Temporal and Spatial Distribution of Heavy Metal in Sediment of Urban Coastal Waters: A Case Study in Jakarta Bay, Indonesia - Fitri Budiyanto; Lestari Lestari (Marine Geological Institute of Indonesia, 2017)
Heavy metals, hazardous chemical substances, increase in marine environment due to anthropogenic discharges. However, due to the hydrodynamic of the marine system these metals could vary both temporal and spatial distribution of metals in Jakarta Bay. This study was to reveal the temporal and spatial distribution of metals in sediment over the bay and to assess the environmental condition. Sediment samples were collected in11 stations of March (transitional season) and June(dry season)2013. The result showed that the concentration of heavy metals varied spatially, in which elevated concentration occurred adjacent terrestrial indicating the enrichment of metal-anthropogenic source, but insignificant temporarily.Keywords: heavy metals, spatial distribution, temporal distribution, anthropogenic activities, Jakarta Bay. Logam berat merupakan bahan berbahaya yang tersebar di lingkungan laut karena pengaruh aktifitas antropogenik. Akan tetapi, logam berat ini dapat terdistribusi secara temporal ataupun spasial di Teluk Jakarta akibat sistem hidrodinamika laut. Tujuan dari penelitian ini adalah untuk mengetahui distribusi spasial dan temporal logam berat dalam sedimen dan untuk menilai kondisi lingkungan teluk. Sedimen diambil dari 11 stasiun pada bulan Maret (musim transisi) dan Juni (musim kering) tahun 2013. Hasil penelitian menunjukkan bahwa distribusi spasial logam berat bervariasi, dimana konsentrasinya meningkat di lokasi dekat daratan yang mengindikasikan tingginya sumber logam-antropogenik namun secara temporal tidak signifikan.Kata kunci: logam berat, distribusi spasial, distribusi temporal, kegiatan antropogenik, Teluk Jakarta.